(untitled) (Mongolian Journal of Chemistry, 2020)
Spinach leaves powder was modified by activation with conc. H2SO4 and was characterized by using FTIR, optical microscopy, XRD analysis and methylene blue adsorption method. The maximum specific surface area measured by the Methylene blue adsorption method was 499 m2/g. The adsorption of iodine was investigated by varying parameters as pH, adsorbent dose, contact time and I2 concentration. The adsorption process was fitted to the Langmuir model controlled by pseudo - second – order kinetics with a constant rate value of 0.00305 g/(mg·min). The maximum adsorption was at pH 10. The maximum adsorption capacity was 909.091 mg/g. The ∆G value was -25 kJ/mole, which confirmed the physico - chemcal adsorption process.